Study of the inhibitory effectiveness of the alcoholic extract of the leaves of Henna plant Lawsonia inermis facing each other bacterial isolates (Journal of the College of Basic Education, 2022)
The aim of the research is to study the effectiveness of the alcoholic extract of the leaves of the henna plant, Lawsonia inermis. In inhibition of three isolates of pathogenic bacteria, namely Klebsiella, Klebsiella pneumonia. oxytoca and planticola Klebsiella by two methods of propagation by etching and by inhibition concentration. The lowest, (MIC). The results of the chemical tests of the active ingredients of henna leaves showed the presence ofTannins, flavones, glycosides, coumarins and resins, and they do not contain soaps. and alkaloids, the hydrogen number of which was (5.2), and when studying the inhibitory effectiveness of the alcoholic extract